The Situation in the Implementation Process of Inclusive Education in the General Education Establishments in Latvia in the Context of Pupils with Special Needs inclusion - Rozenfelde, Mārīte (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The article highlights the role of attitudes, competences and experience in practical inclusive action of contemporary general education teachers working at inclusive education schools to create and facilitate an inclusive education process referring to the Profile of Inclusive Teachers published by the European Agency for Special Education Development in 2012 identifying four basic values of teaching and learning which are the basis of all teachers’ action in inclusive education. These basic values are related to the areas of teacher’s competences including three elements: attitudes, knowledge and skills. There are provided the results of the survey of 2013 on the attitude of teachers in Latvia implementing inclusive education and teachers’ view on the problems existing in the inclusive education process and their solution in on the national level.